Movimentos e articulações: uma análise das iniciativas de formação de educadoras/es em sexualidade na Rede Municipal de Educação de Belo Horizonte (1989-2009) - Anna Claudia Eutropio Batista D''andrea (2014)
The research herein presented aims at analyzing the initiatives to form educators for the work in sexual education at the Municipal Educational Network of the city of Belo Horizonte, from 1989 to 2009. By means of a case study in the city of Belo Horizonte, seven interviews with retired and current employees of the city administration were carried out and documents were analyzed. An emancipating approach towards sexual education was opted, which means dealing with the issue, under a historically inserted perspective, and in a way committed to the transformation of society towards gender equality and upholding sexual diversity. Afro-American feminist Bell Hooks and Brazilian educators Paulo Freire and Miguel Arroyo, the field studies in the formation of teachers and sexual education, make up the analytical framework. Regarding empirical data, the initiatives of formation were organized in four movements: regional articulation, whose landmark was the Center of Affective Sexual Education (Núcleo de Educação Afetivo Sexual - NEAS), in the Barreiro regional administration; municipal articulation, which shows the existence of initiatives of formation of educators in sexuality in Belo Horizonte, coordinated by the Municipal Secretary of Education (Secretaria Municipal de Educação - SMEd-BH); cross-sector articulation, which reveals the link between health and education in the Program BH de Mãos Dadas contra a AIDS (BH holding hands against AIDS); and, finally, cross-institutional articulation, in which the Federal University of Minas Gerais, the Ministry of Education (MEC), the SMEd-BH Center of Ethnical-Racial and Gender Relations (Núcleo de Relações Étnico-raciais e de Gênero), and social movements gather and put forward the project Educação sem Homofobia (Homophobia-free education). By analyzing such initiatives, one realizes that none of them displays a single approach to sexual education and are all noted for their hybridism. Regarding the models of formation of teachers, the analysis reinforces the importance of critical reasoning for forming educators in sexuality. It is still necessary to strengthen the teachers role in the initiatives of formation and bring about a real shift in the locus of formation, with a view to the institutional development of the schools. Based on the analyzed initiatives, it is understood that one path for the formation of educators is to not champion a single way to express sexuality and not prescribe didactic approaches. A dialogical process is created, in which knowledge can be shared, questioned, advanced, seeking to uphold diversity and legitimacy of difference. In order to do so, it is paramount to understand the broader discussion which encompasses sexuality, questioning the political-ideological bases of an exclusively preventive sexual education.